Hotel Advisory System / Norizan Mat Jusoh - Norizan, Mat Jusoh (2006)
Nowadays, finding a suitable hotel that base on the customer preferences is a very difficult task especially for those who do not have enough time. Regularly, people find the hotel by using search engine likes yahoo and goggle but the problem occur when they display many result and the user must take a time to analyze each list of hotel that match their hotel preference. At this point, the user is facing difficulties to get the best choices. This report describes the research and development of the prototype system; called Hotel Advisory System (HAS). So, HAS is develop with the purpose to help the user to provide the list of the suitable hotel that match all of the characteristics that has been required by them. Furthermore, if they agree with the result then the system will help them to make online reservation directly. This system uses expert system as a metiiod in order to produce the result. HAS is implemented on personal computers imder a Microsoft Windows environment. The system design is developed using Macromedia Dream weaver as the web application tools, Internet Information Services (IIS) as a web server and Microsoft Access as the database. The system will perform their task by providing only a list of hotel in Selangor or Kuala Lumpur area that match with all of the criteria that has been select by the user. The result is very useftil to the user in order to help them choose the best hotel to enjoy their holiday. The results of the prototype evaluation were satisfactory and support the contention that HAS performs its fimctions as expected.